Multi-Scale Approach and “Playing Scales” in Economic Geography - Jakobson, Anatol; Blinov, Ivan D. (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2014)
The notions of multiscaleness and “playing scales” are considered for various spheres of economic geography: cartography, settlement geography, toponymics, ethno-historical geography, locating industrial production, touristic promotion, micro-regional (intra-urban) policy. The paper presents the idea of multiscaleness and “playing scales”, as well as the possibility of application of a multi- scale approach in economic geography.